NTU a 'China' university : the manifestation of 'New Racism' in NTU - Bathusha, Thasneem (2017)
The tension between citizens and immigrants is evidently present in the socio-political landscape of Singapore. The Singaporean Chinese citizens exhibit prejudice towards immigrants from China despite their co-ethnicity, a trend indicative of the rise of 'new racism'. Interestingly, such prejudice is also exhibited towards an institution such as Nanyang Technological University (NTU) which is stigmatised as a 'China' university. A qualitative study was undertaken to identify the factors behind NTU's image as well as to understand the influence of 'new racism' on the interactions between Singaporean Chinese students and students from China studying in NTU. The findings reveal how the Chinese heritage, substantial presence of students from China due to state policies and the presence of certain symbols have contributed to the stereotypical labelling of the university. The findings also identified discourses which shape the interactions between the two groups of students and the perceptions which arise from the interactions.